1991
DOI: 10.1111/j.1476-5381.1991.tb12511.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbenoxolone on the biological activity of nitric oxide: relation to gastroprotection

Abstract: 1 The interactions between carbenoxolone and nitric oxide (NO) were examined by investigating their effects on human platelet aggregation, on rat aortic strips precontracted by phenylephrine and on protection of rat gastric mucosa against ethanol-induced injury.2 Carbenoxolone (100-300,UM) caused a significant and concentration-dependent potentiation of rat peritoneal neutrophil (RPN)-, 3-morpholino-sydnonimine (SIN-1)-or iloprost-induced inhibition of platelet aggregation. Higher concentrations (5001uM) of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…7). Similar effects have been observed after administration o f 'cytoprotective' drugs such as carbenoxolone [76], sucralfate [77] or aluminum-containing antacids [78] whose protective activity was reduced by the inhibition of NOS and reversed by the addition of L-argi- 8 …”
Section: Implication Of No In Gastric Cytoprotectionsupporting
confidence: 48%
“…7). Similar effects have been observed after administration o f 'cytoprotective' drugs such as carbenoxolone [76], sucralfate [77] or aluminum-containing antacids [78] whose protective activity was reduced by the inhibition of NOS and reversed by the addition of L-argi- 8 …”
Section: Implication Of No In Gastric Cytoprotectionsupporting
confidence: 48%
“…Recent studies showed that NO plays an important role in the modulation of the gastric mucosal integrity by interacting with sensory neuropeptides and endogenous prostaglandins (PGs) (3 5). It has been also shown that endogenous NO is involved in certain types of gastro protection as induced by capsaicin (6), carbenoxolone (7) and mild irritants (8). However, the effect of L-arginine, the precursor of NO, on the gastric mucosal integrity has not been much studied.…”
mentioning
confidence: 99%
“…Recent studies showed that NO could be involved in the protective actions of some antiulcer drugs such as car benoxolone and sucralfate (8,15). Lambrecht and Peskar (9) examined the effect of L-NNA pretreatment on the pro tective actions of some mild irritants against ethanol-in duced gatric lesions and found that L-NNA counteracted the protective action by 20% ethanol and 0.1 N NaOH but not that by 0.3 N HC1 and 5016 NaC1, suggesting that NO is involved in the protective activity of some but not all mild irritants.…”
Section: Discussionmentioning
confidence: 99%